Geospatial and AHP based identification of potential zones for groundwater recharge in Haridwar District of India - Pirasteh, Saied; Samad, Abdul; Ahmad, Rizwan; Thakural, L. N.; Khan, Haris Hasan; Chauhan, Pankaj; Khan, Arina; Qamar, Mohammed Zaid (Frontiers in Environmental Science, 2025)
Demarcation of the groundwater recharge prospective zones can be the foremost step in facilitating groundwater recharge in any terrain, as most nations have a major concern about unreasonable use of groundwater and declining the water table. To identify groundwater recharge zones in Haridwar district of Uttarakhand state in India, this study employs the integration of remote sensing data along with the Geographical Information System (GIS) and the Analytical Hierarchy Process (AHP) technique by incorporating remote sensing data acquired from different sources. Soil texture, slope, drainage density, land use/land cover (LULC), lithology, geomorphology, lineament density, topographic wetness index (TWI), and rainfall were analysed, and weights were assigned using the AHP technique to assess their impact on groundwater recharge. The study region has been divided into five possible groundwater recharge zones by using weighted overlay analysis: very high (0.82%), high (37.03%), moderate (40.22%), low (17.91%), and very low (4.02%). The verified groundwater recharge potential map for the study region has been validated with 30 existing bore wells. The efficacy of the method was confirmed by an Area Under Curve (AUC) calculated to be 71.08% with the evidence obtained, and the Receiver Operating Characteristic (ROC) curve is plotted. The findings facilitate the sustainable management of groundwater and the application of artificial recharge techniques in Haridwar.